2019
DOI: 10.3847/2041-8213/ab3c5f
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the Weak Equivalence Principle and Photon Mass with FRB 121102 Subpulses

Abstract: Fast radio bursts (FRBs) are short duration (∼millisecond) radio transients with cosmological origin. The simple sharp features of the FRB signal have been utilized to probe two fundamental laws of physics, namey, testing Einstein's weak equivalence principle and constraining the rest mass of the photon. Recently, Hessels et al. (2018) found that after correcting for dispersive delay, some of the bursts in FRB 121102 have complex time-frequency structures that include sub-pulses with a time-frequency downwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 84 publications
(99 reference statements)
1
54
0
Order By: Relevance
“…Thirdly, the massive photon group velocity differs from c by a quantity proportional to the inverse of the frequency squared [9][10][11]23]. Such a dependence has been analysed recently with the signals from Fast Radio Bursts (FRBs) [79][80][81][82][83][84][85][86][87][88].…”
Section: Time Dilation and Supernovaementioning
confidence: 99%
“…Thirdly, the massive photon group velocity differs from c by a quantity proportional to the inverse of the frequency squared [9][10][11]23]. Such a dependence has been analysed recently with the signals from Fast Radio Bursts (FRBs) [79][80][81][82][83][84][85][86][87][88].…”
Section: Time Dilation and Supernovaementioning
confidence: 99%
“…We aim to find the constraint on Δ𝛾. According to our understanding from various previous studies (Tingay & Kaplan 2016;Nusser 2016;Xing et al 2019;Bartlett et al 2021;Li et al 2021;Yang et al 2020;Tangmatitham & Nemiroff 2019), we can only consider the upper limit of Δ𝛾 value to mark a constraint which essentially indicates an upper limit of the violation of WEP. According to our calculation from Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…If both the violation of WEP and Δ𝑡 DM show an equivalent dependence on 𝜈 −2 obs , the two effects are not distinguishable (Ioka 2003;Macquart et al 2020;Inoue 2004). Until now, current studies of FRBs or any other sources have not found any such violation due to frequency (Einstein 1908;Tingay & Kaplan 2016;Nusser 2016;Minazzoli et al 2019a;Xing et al 2019).…”
Section: Theoretical Modelmentioning
confidence: 97%
“…Calculating the difference of the γ value between different particles ∆γ can constrain the accuracy of the EEP. Now, the extragalactic transients have been used to the constrains on EEP or Einstein's Weak Equivalence Principle (WEP) [268][269][270][271][272].…”
Section: Weak Equivalence Principlementioning
confidence: 99%